Potential of anticoagulant therapy in cardiology practice for thrombocytopenia. Literature review - K. G. Pereverzeva; S. S. Yakushin; A. An. Korshikova (Российский кардиологический журнал)
The review article discusses the issues of anticoagulant therapy in cardiovascular patients with thrombocytopenia (TP), gives the concept of ethylenediaminetetraacetic acidand heparin-induced TP. The management of patients with heparin-induced TP is analyzed in detail, which consists in the discontinuation of unfractionated and low molecular weight heparin administration with replacement to direct thrombin inhibitors (lepirudin or argatroban), fondaparinux or direct oral anticoagulants.The authors emphasize that the anticoagulant administration to most patients with platelet count >50×109/l is possible in full prophylactic and therapeutic doses. Reducing the level of platelets to 25-50×109/l in most cases requires a reduction in the anticoagulant dose by 50%. At a platelet level of 20-25×109/l or less, anticoagulant therapy should be avoided in most patients.In addition to the scope of anticoagulant therapy, TP also determines the choice of anticoagulant as follows: in patients with acute coronary syndrome, bivalirudin or fondaparinux are recommended, while in patients with cancer and stable TP, warfarin or direct oral anticoagulants can be prescribed. In progressive TP (if heparin-induced TP is ruled out), low molecular weight heparins should be used.